Measuring and improving the quality of tuberculosis care: A framework and implications from the Lancet Global Health Commission. (August 2019) - Arsenault, Catherine; Roder-DeWan, Sanam; Kruk, Margaret E.
Abstract: In this article, we describe the framework of the Lancet Global Health Commission on High Quality Health Systems, propose new and undermeasured indicators of TB care quality, and discuss implications of the Commission's key conclusions for measuring and improving the quality of TB care services. The Commission contends that measurement of quality should focus on the processes of care and their impacts. In addition to monitoring treatment coverage and the availability of tools, governments should consider indicators of clinical competence (for e.g. ability of providers to correctly diagnose TB and adhere to treatment guidelines), of timely, continuous and integrated care and of respectful and patient-centered care. Indicators of impact include TB mortality and treatment success rates, but also quality of life and daily functioning among TB patients, public trust in TB services, and bypassing of the formal health system for TB care. Cascades of care, from initial care seeking to recurrence-free survival, should be built in every high-burden country to monitor quality longitudinally. In turn, improvement efforts should target the foundations of health systems and consider the Commission's four universal actions: governing for quality, redesigning service delivery, transforming the health workforce and igniting demand for quality TB services. Important work remains to validate new indicators of TB care quality, develop data collection systems for new measures, and to test new strategies for improving the delivery of competent and respectful TB care.